2018
DOI: 10.3389/fmicb.2018.01294
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell MALDI-TOF MS Versus 16S rRNA Gene Analysis for Identification and Dereplication of Recurrent Bacterial Isolates

Abstract: Many ecological experiments are based on the extraction and downstream analyses of microorganisms from different environmental samples. Due to its high throughput, cost-effectiveness and rapid performance, Matrix Assisted Laser Desorption/Ionization Mass Spectrometry with Time-of-Flight detector (MALDI-TOF MS), which has been proposed as a promising tool for bacterial identification and classification, could be advantageously used for dereplication of recurrent bacterial isolates. In this study, we compared wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 73 publications
8
94
0
1
Order By: Relevance
“…On the contrary, the isolates WG29 and WG35 grouped within one cluster according to MALDI-TOF MS Biotyper did not reflect 100% similarity according to the 16S rDNA analysis. This is in accordance with the opinion of Strejcek et al [ 25 ], who established that, although whole-cell MALDI-TOF-based identification of bacterial isolated is in general agreement with the results of 16S rRNA gene sequence analysis, high accordance was confirmed merely up to the genus level. Nevertheless, at the species level, the agreement appeared to be limited.…”
Section: Resultssupporting
confidence: 92%
“…On the contrary, the isolates WG29 and WG35 grouped within one cluster according to MALDI-TOF MS Biotyper did not reflect 100% similarity according to the 16S rDNA analysis. This is in accordance with the opinion of Strejcek et al [ 25 ], who established that, although whole-cell MALDI-TOF-based identification of bacterial isolated is in general agreement with the results of 16S rRNA gene sequence analysis, high accordance was confirmed merely up to the genus level. Nevertheless, at the species level, the agreement appeared to be limited.…”
Section: Resultssupporting
confidence: 92%
“…Strejcek et al [44] also compared whole-cell MALDI-TOF MS with 16S rRNA gene analysis for identification of recurrent bacterial isolates. The authors confirmed the potential of MALDI-TOF MS as a rapid screening method in environmental microbiology for determining similarities between bacterial isolates at genus level with various limitations such as low number of peaks, availability of reference mass spectra of only well-studied and described strains in database, etc.…”
Section: Comparative Assessment Of Psychrotolerant Bacteria Using 16smentioning
confidence: 99%
“…We compared the outcome of SPeDE dereplication for the benchmark data set to that of previously described methods based on (i) the global Pearson product moment correlation and the unweighted pair group method with arithmetic mean (UPGMA) clustering proposed by Ghyselinck and colleagues (21) and (ii) the cosine similarity/UPGMA clustering described by Strejcek and colleagues (22). The results are given in Table S3 and Table S4, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The method of Ghyselinck et al (21) returned the most OIUs, retrieved the least diversity from the benchmark data set, and had the overall longest processing time (Table 1). The method of Strejcek and colleagues (22), based on a proposed cosine similarity cutoff of 92%, was the best performing in terms of overall dereplication ratio, with a reduction of 97% of the spectra for the benchmark data set. However, the analysis also returned 15 OIUs which included multiple genetically distinct strains, with 1 OIU merging strains sharing less than 92% genome-wide ANI (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation